THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT THE SINAR LAUNDRY BUSINESS IN GOWA DISTRICT - Ananda Roni Pratami; Agus Syam, Muhammad Jufri, Asmayanti, Nur Halim (BORJUIS: JURNAL OF ECONOMY, 2024)
This research is aimed at finding out the impact of the quality of service on the client. This type of research is included in research research using a quantitative approach. Its independent variable is the quality of service while its dependent is customer satisfaction. The population in this study was a customer of Sinar Laundry in Gowa District. The sample used in this study was 97 clients. Data collection is done by distributing questionnaires to respondents. The data analysis technique used is simple linear regression analysis using SPSS 24 software. Based on the results obtained the significant value (Sig) is 0,000 which is less than 0.05 so it can be concluded that the quality of service has an influence on customer satisfaction on the Sinar Boat business in Gowa District.